2009
DOI: 10.1590/s0066-782x2009001100006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de síndrome metabólica em pacientes de um ambulatório do Instituto de Cardiologia do Rio Grande do Sul (RS)

Abstract: Background: Metabolic syndrome (MS) is considered a very important factor in the development of cardiovascular diseases (CVD).Objective: To assess the prevalence of metabolic syndrome (MS) in outpatients undergoing secondary prevention of coronary artery disease in the Institute of Cardiology, University Foundation of Cardiology -IC-UFC, as well as to detect excess weight through body mass index (BMI) and the prevalence of abdominal obesity in patients with cardiovascular disease (CVD). Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
2
2
1
5
Order By: Relevance
“…In our study, AO is inversely correlated with HDL-C and match up to different population studies. 28,29 Among our urban elderly Tirupati town participants, we found that female sex, age (particularly those >74 years of age), and high BMI (those overweight and obese), increased the MetS risk; high education level (higher than high school) decreased the MetS risk and these outcomes allied to the studies of Hydrie et al, Mabry et al, and Prasad et al 14,17,18 Other factors showed no significant differences in multiple logistic regression. It may be assumed that enhancing health consciousness in the public and establishing a regular screening system may enable early detection of those at risk for developing MetS.…”
Section: Discussionsupporting
confidence: 52%
“…In our study, AO is inversely correlated with HDL-C and match up to different population studies. 28,29 Among our urban elderly Tirupati town participants, we found that female sex, age (particularly those >74 years of age), and high BMI (those overweight and obese), increased the MetS risk; high education level (higher than high school) decreased the MetS risk and these outcomes allied to the studies of Hydrie et al, Mabry et al, and Prasad et al 14,17,18 Other factors showed no significant differences in multiple logistic regression. It may be assumed that enhancing health consciousness in the public and establishing a regular screening system may enable early detection of those at risk for developing MetS.…”
Section: Discussionsupporting
confidence: 52%
“…Nos pacientes estudados, a principal etiologia da doença renal crônica encontrada foi hipertensão arterial sistêmica (HAS) com 37% (13) , seguida de Diabetes mellitus (DM) com 17% (6) e rins policísticos com 11% (4) , sendo que as outras causas somaram 34% (12) . A figura 1 apresenta dados do IMC inicial e do IMC após doze meses em DP.…”
Section: Resultsunclassified
“…Dos 35 pacientes estudados, 34% (12) foram desligados do programa de diálise peritoneal a partir de janeiro de 2010, sendo 42%…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Here, it should be emphasized that this was a service for secondary prevention in specialized clinics. In other words, the individuals of the sample had already previously been diagnosed with cardiovascular disease (Bopp & Barbiero, 2009). Other authors studied the prevalence of MS and its components through the agreement of two diagnostic criteria in a population of 719 patients aged more than 13 years, who attended outpatient cardiology clinics in a capital of the region of the Brazilian Northeast.…”
Section: Quality Of Life and Health Of Military Policemenmentioning
confidence: 99%